2022
DOI: 10.1093/oncolo/oyac196
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seropositivity After Standard Doses of Vaccination Against SARS-CoV-2 in Patients With Early Breast Cancer Receiving Adjuvant Treatment

Abstract: Background Coronavirus disease 2019 (COVID-19) pandemic affected millions of individuals, and patients with cancer are known to be more susceptible. Vaccines against SARS-CoV-2 have been developed and used for patients with cancer, but scarce data are available on their efficacy in patients under active anti-cancer therapies. Materials and Methods In this study, we semi-quantitatively measured the titers of the immunoglobulin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A significant number of studies have shown that humoral immunity was comparable to that of healthy controls after two doses, similar to our results. 2 17 18 However, other studies have shown lower immunogenicity in cancer patients compared to healthy controls. 5 6 7 This difference is due to the heterogeneity of cancer patients, and for a comprehensive understanding of immunogenicity in cancer patients, it is necessary to conduct studies on a wide range of patients.…”
Section: Discussionmentioning
confidence: 96%
“…A significant number of studies have shown that humoral immunity was comparable to that of healthy controls after two doses, similar to our results. 2 17 18 However, other studies have shown lower immunogenicity in cancer patients compared to healthy controls. 5 6 7 This difference is due to the heterogeneity of cancer patients, and for a comprehensive understanding of immunogenicity in cancer patients, it is necessary to conduct studies on a wide range of patients.…”
Section: Discussionmentioning
confidence: 96%
“…The type of cancer, its histopathological characteristics and its stage of advancement generate differently intense and targeted immune responses [13]. The question, therefore, arises whether some cancers do not naturally generate a more excellent humoral response directed against the SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design was a prospective longitudinal cohort study. Patients with early breast cancer who were 20 years or older and received systemic anti-cancer treatments for breast cancer at Seoul National University Hospital (SNUH) were recruited as in previous study ( 23 ). Controls were healthcare workers at SNUH who did not have any systemic diseases.…”
Section: Methodsmentioning
confidence: 99%